SELF-EFFICACY REDUCES RELAPSE IN DRUG ABUSE WITH COGNITIVE BEHAVIOUR THERAPY - Susanti, Meri; Dania, Ira Aini; Ibarra, Florante (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
Maladaptive substance abuse (NAPZA) can lead to clinically significant disorders. According to the National Narcotics Agency (BNN) states that around 90 percent of former drug addicts who undergo the rehabilitation process experience a relapse and return to abusing drugs. The research results show that cognitive Behaviour Therapy (CBT) is an effective intervention method in treating drug abuse. This research aims to test the effectiveness of cognitive behavior therapy to increase self-efficacy to reduce the risk of relapse in drug abusers. The study used a pre-posttest experimental method with a control group. Research respondents were selected using a purposive sampling technique with a sample size of 30 people. Both groups were given the Drug Abstinence Self-Efficacy Scale (DASES) measurement to see the effectiveness of applying cognitive behavior therapy in increasing self-efficacy in addicts who have participated in the rehabilitation program. The change in self-efficacy in both groups from medium to high was 66.7% after the intervention. A comparison between the two groups was made before the intervention, where the significance value was p = 0.399, and after the intervention, there was a change in the score between the two groups to 0.001. There was a significant difference between the two groups before and after the intervention, with a value of p = 0.001. Meanwhile, there was no substantial change in the control group in p=0.177. CBT is effective in increasing abstinence self-efficacy in drug addicts as an effective therapy to reduce the risk of relapse in drug addicts in rehabilitation programs